Beta and alpha cell function in metabolically healthy but obese subjects: Relationship with entero‐insular axis1. (26th March 2013) - Calanna, Salvatore; Piro, Salvatore; Di Pino, Antonino; Maria Zagami, Rose; Urbano, Francesca; Purrello, Francesco; Maria Rabuazzo, Agata
Abstract Objective: Obesity is widely acknowledged as a critical risk factor for metabolic complications. Among obese subjects, there is a phenotype of metabolically healthy but obese (MHO) individuals that shows a favorable cardiometabolic risk profile. We aimed to evaluate the potential mechanisms underlying the metabolic profile of this subset, including alpha and beta cell function and entero‐insular axis. Design and Methods: One hundred twenty‐nine obese and 24 nonobese subjects were studied. Obese participants were defined as MHO or at‐risk obese, according to the homeostasis model of assessment‐insulin resistance (HOMA‐IR) index (MHO: lower tertile of HOMA‐IR, n = 43; at‐risk: upper tertile of HOMA‐IR index, n = 41). Insulin, glucagon, and incretin responses after a 120′ oral glucose tolerance test (75‐g OGTT) were investigated. Results: During OGTT, MHO individuals showed in comparison with at‐risk subjects: lower fasting and afterloads plasma levels of glucose, insulin, and C‐peptide; higher disposition index; lower fasting (P = 0.004) and at 30′ (P = 0.01) plasma glucose‐dependent insulinotropic polypeptide (GIP) levels; lower area under the curve (AUC) (0‐30) for GIP (P = 0.008); higher glucagon‐like peptide‐1 (GLP‐1) plasma levels at 90′ (P = 0.02) and 120′ (P = 0.02); lower glucagon plasma levels at baseline (P = 0.04) and at 30′ (P = 0.03); and appropriate glucagon suppression after the oral glucose load. Conclusions: MHO subjects show, as well as normal‐weight individuals, a lower diabetogenic profile by virtue of higher disposition index and unaffected entero‐insular axis. At‐risk obese individuals present increased GIP levels that might play a role in determining increased glucagon secretion and inappropriate glucagon responses after glucose load, thus contributing to impaired glucose homeostasis.